Applied mathematics for business, economics, and the social sciences - Budnick, Frank S. (McGraw-Hill, 1979)
This book was required for my BBA class, So I when bought it, I was expecting it the same as all other boring math books i had bought but I found it so much interesting and easy to understand, although so many other applied mathematics and calculus books are available in the market but none of them has provided the comprehensive material as this book have. variety of topics are included for the different kind of students from different background and subjects.